2022
DOI: 10.1155/2022/9979683
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Amino Acid Changes in the Fusion Protein of Virulent Newcastle Disease Virus from Vaccinated Poultry in Nigerian Isolates

Abstract: The roles of fusion gene in the virulence of Newcastle disease virus are well established, but the extent of its variation among the XIV, XVII, and XVIII genotypes reported in Central Africa and West Africa has until recently been understudied. In this study, virulent Newcastle disease virus (vNDV) was isolated from dead chickens among vaccinated flocks between March and April 2020. Fusion (F) gene was sequenced and analysed for characterization and information about genetic changes. Many substitutions were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(78 reference statements)
0
1
1
Order By: Relevance
“…The present study demonstrated the isolation of NDV in broiler and village chickens sold at a LBM in Lusaka and wild birds in the LNP, with a positivity rate of 0.3% and 0.07%, respectively. The positivity rate of NDV recorded in chickens at LBMs in the current study was lower than 4.36-91.67% reported in Ghana and Tanzania [29], 65.9% in Egypt [30], 54% in Nigeria [31], and 45% in Libya [32]. Moreover, the positivity rate of NDV in wild birds was also lower compared to 2-10% reported in other African countries [28,[33][34][35].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The present study demonstrated the isolation of NDV in broiler and village chickens sold at a LBM in Lusaka and wild birds in the LNP, with a positivity rate of 0.3% and 0.07%, respectively. The positivity rate of NDV recorded in chickens at LBMs in the current study was lower than 4.36-91.67% reported in Ghana and Tanzania [29], 65.9% in Egypt [30], 54% in Nigeria [31], and 45% in Libya [32]. Moreover, the positivity rate of NDV in wild birds was also lower compared to 2-10% reported in other African countries [28,[33][34][35].…”
Section: Discussioncontrasting
confidence: 83%
“…The observed difference in the positivity rates could be attributed to the differences in the health status of the birds sampled, the type of samples collected, and the methods of detection used. For example, other studies collected organ samples and cloacal or oropharyngeal swabs from sick or both sick and apparently healthy birds and used RT-PCR for detection [ 31 , 32 ], which may increase the detection rate. The low isolation rate of NDV in poultry could indicate some success in containing the disease through ND vaccinations in the country.…”
Section: Discussionmentioning
confidence: 99%